TGIFLY mRNA Expression in Human Testis with Spermatogenesis Defects - M Heidari; Z Ousati- Ashtiani; MH Modarressi; M Aarabi (Tehran University of Medical Sciences, 2008)
Background: Hox genes are well-known transcription factors that play essential roles in directing embryonic development. TGIFLY is a Y-linked homeobox gene that was originally identified by virtue of its expression in adult testis. The functions of TGIFLY in normal and abnormal development are unknown. Methods: To investigate the potential roles of TGIFLY gene in the infertile males, a semi-nested Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) was performed on the testicular samples of 110 patients with non-obstructive azoospermia. Results: The expression of TGIFLY in 59(53.6%) out of 110 patients were undetectable. Patients with different spermatogenesis defects failed to show the expected in TGIFLY gene expression as demonstrated in the normal testes. Conclusion: Our results indicate that TGIFLY is expressed in testis and could be associated with infertility in patients with azoospermia. TGIFLY may be required for the regulation of spermatogonial stem cell specification and proliferation that is essential to the establishment and maintenance of spermatogenesis in human.